2006
DOI: 10.2753/mis0742-1222230311
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge Management Success Model: Theoretical Development and Empirical Validation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Ronald Freeze is a visiting Assistant Professor of Information Systems at the W.P. Carey School of Business, Arizona State University. He received his Ph.D. in Information Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
398
3
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(441 citation statements)
references
References 46 publications
24
398
3
16
Order By: Relevance
“…Moreover, some authors have found a positive relationship between information quality and usefulness (Kositanurit, Ngwenyama, & Osei-Bryson, 2006;Rai et al, 2002), while others have found a non-significant relationship between them. For instance, in the context of a knowledge management system, Kulkarni, Ravindran, and Freeze (2007) attribute that nonsignificance to the fact that those systems are in an incipient stage, and the information stored in them does not yet help individuals to perform specific tasks. Adams, Nelson, and Todd (1992) found a similar problem-i.e., mixed results-when exploring the relationship between ease-of-use and system use.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors have found a positive relationship between information quality and usefulness (Kositanurit, Ngwenyama, & Osei-Bryson, 2006;Rai et al, 2002), while others have found a non-significant relationship between them. For instance, in the context of a knowledge management system, Kulkarni, Ravindran, and Freeze (2007) attribute that nonsignificance to the fact that those systems are in an incipient stage, and the information stored in them does not yet help individuals to perform specific tasks. Adams, Nelson, and Todd (1992) found a similar problem-i.e., mixed results-when exploring the relationship between ease-of-use and system use.…”
Section: Introductionmentioning
confidence: 99%
“…This research employed a five-point measurement from 1.dissatisfied to 5.very satisfied with the achievements in knowledge management in the three recent years to evaluate the construct of knowledge management, slightly modified from previous research (Gold et al 2001;Lin and Lee 2005). Usefulness of Knowledge Management (UKM) is measured on a five-point construct ranging 1.not at all useful to 5.very useful (following Kulkarni et al (2007). Firm ISSN 2162-3082 2017 Structure (FS) is evaluated on three items.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge management usefulness is suggested as the effectiveness of knowledge management perceived by users on their work performance and efficiency (Kulkarni et al 2007). Those researchers also confirm a very possible link between knowledge management usefulness and its acceptance.…”
Section: Determinants Of Knowledge Managementmentioning
confidence: 99%
“…In most KMS, however, only a small percentage of users routinely contribute knowledge; for most users, routine KMS use means reusing the knowledge that others have contributed (Ko & Dennis, 2011;Kulkarnin et al, 2006;Marks, Polak, McCoy, & Galletta, 2008).…”
Section: Knowledge Management Systemsmentioning
confidence: 99%
“…Many firms have implemented enterprise-wide KMS in recognition of the strategic importance of organizational knowledge management (Alavi & Leidner, 1999;Hansen, Nohira, & Tierney, 1999). Much research suggests that a KMS can help an organization manage its organizational knowledge processes (Alavi & Leidner 1999 although measuring the success and organizational impact of a KMS can be challenging (Jennex & Olfman, 2006;Jennex et al, 2012;Ko & Dennis, 2011;Kulkarnin, Ravindrin, & Freeze, 2006).…”
Section: Knowledge Management Systemsmentioning
confidence: 99%